Metabolic Syndrome in Patienet with Hypothyroidism Presenting in a Tertiaty Care Hospital - Saima Rasheed, Maheen Altaf, Zaryab Shafiq, Abdul Rahman Abid, Tabinda Kazmi, Muhammad Zubair, Usama Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
This trial aimed to record the frequency of metabolic syndrome (MetS) in patients presenting with hypothyroidism. Methods: This cross-sectional study was conducted at Niazi Medical and Dental College, Sargodha during Nov 21 to April, 22. We included a total of 130 diagnosed cases of hypothyroidism, a pre-designed questionnaire was used to note patients with hypothyroidism by individual interview and noting demographic data i.e. age, gender, thyroid profile (TSH, T3 and T4). Metabolic syndrome was documented using the standard set of criteria i.e. measurement of waist circumference, blood pressure measurement.3 ml of venous blood was drawn by a trained phlebotomist and sent to biochemistry laboratory for serum triglycerides, HDL cholesterol and fasting blood sugar levels. Results: Of the 130 cases, 37.69% (n=49) were up to 50 years of age and 62.31% (n=81) had age >50 years, 28.46% (n=37) were male and (n=93)71.54% females. We found 71.54%(n=91) cases with metabolic syndrome. Conclusion: Hypothyroidism plays an important role in MetS. Routine screening in patients with hypothyroidism may unmask MetS.